HISTORY OF VJING ARIRISING AS A GENRE OF MODERN MEDIA ART - ГАБРЕЛЬ, Т. М. (Art and Design, 2022)
Goal: declare and reveal the essence of the concept of "VJing" as an original form of modern media art; on the basis of historical analysis to reveal the achievements of iconic personalities involved in the origin and development of the genre. Methodology: retrospective analysis and analysis of literature sources. Results. The contribution of a number of personalities who gave impetus to the formation of a new artistic direction is singled out and characterized; their creative way and own creative method are analyzed. The originality of the new trend of space-time art and its relationship with the development of media technologies is shown. The importance of the synthesis of pictorial means that shape the visual aesthetics, technical and technological skills and erudition of the performer, and the content itself in media works is emphasized. Priority areas for further research in the field of media art are outlined. VJing as a form of modern media art, aimed at regular search for new topics and constant movement forward; the rapid expansion of VJing is inextricably linked with the development of media technologies; the importance of using one's own creative potential to express meaningful ideas; When linking the personalities of innovators with technologies that regularly expand the possibilities of media art, it is important to focus on the content. Scientific novelty. For the first time in the scientific art literature of Ukraine the concept of "VJing" is considered and analyzed and the creators who expanded the concept of modern art under the influence of technology are named. Practical significance. The history of VJing as a modern original art form is analyzed by analyzing key personalities in this field and identified the founders of the genre. The work and credo of the marked pioneers of the genre, which is done for the first time in Ukrainian art literature, are analyzed. The relationship between the development of technology and the formation of new art forms is shown.